The Factor V R2 Allele: Risk of Venous Thromboembolism, Factor V Levels and Resistance to Activated Protein C - Luddington, Roger; Jackson, Andrew; Pannerselvam, Sabapathy; Brown, Karen; Baglin, Trevor (Thrombosis and Haemostasis, 2000)
Case-control studies have yielded conflicting results regarding the relative risk of venous thromboembolism associated with the factor V R2 allele. We calculated odds ratios in 581 patients and 469 agematched controls. The odds ratio for the R2 allele in patients relative to controls was 1.21 (95% CI 0.84 to 1.74). These results do not support the hypothesis that the R2 allele is a risk factor for venous thromboembolism. There was no relationship between factor V levels and R2 carrier status. Normalised APC sensitivity ratios were not lower in carriers of the R2 allele. In an in vitro model progressive APC resistance was observed with factor V levels of 60% and less but ratios less than 2.4 (equivalent to a normalised ratio of 0.73) did not occur until factor V levels were less than 20%. The relationship between APC resistance and factor V level was not observed in a factor VIII-independent model.
Keywords: Factor V; HR2 haplotype; R2 allele; APC resistance; thrombosis